2021
DOI: 10.1002/oby.23298
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood social cohesion and physical activity and obesity outcomes among Native Hawaiian and Pacific Islander individuals

Abstract: Objective Native Hawaiian and Pacific Islander (NHPI) individuals report high obesity rates and low physical activity (PA) levels. This study examined associations between neighborhood social cohesion, obesity, and PA among NHPI adults. Methods Cross‐sectional data from the 2014 NHPI National Health Interview Survey were analyzed. Social cohesion was assessed using a summative scale and categorized as low, medium, and high. PA was measured via self‐report and categorized as insufficiently active (0‐149 min/wk)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Additionally, our survey population was selected by case-control matching on cardiovascular disease status with oversampling of Asian and Pacific Islander racial and ethnic groups. Although our results are similar to those of previous studies, 7,8,[31][32][33]…”
Section: Strengths and Limitationssupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, our survey population was selected by case-control matching on cardiovascular disease status with oversampling of Asian and Pacific Islander racial and ethnic groups. Although our results are similar to those of previous studies, 7,8,[31][32][33]…”
Section: Strengths and Limitationssupporting
confidence: 92%
“…However, when applying Asian-specific BMI cutoffs, the prevalence of obesity among single-race Asian groups was similar to that among single-race White individuals. Moreover, we found that obesity prevalence was higher among Pacific Islander groups compared with Asian groups and White individuals …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations